Analysis of the Influence of Price, Service Quality and Customer Experience on Customer Loyalty - Hanum, Fadillah; Jannah, Nurul; Soemitra, Andri (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Customer loyalty in workshops refers to the commitment and dedication of customers to the services provided by a particular workshop. This is reflected in their tendency to repeatedly use the services, recommend them to others, and reject offers from competing workshops, even when accompanied by attractive promotions or incentives. This study aims to analyze the influence of price, service quality, and customer experience on customer loyalty. Using a quantitative descriptive approach, data were collected through questionnaires distributed to workshop customers, with purposive sampling yielding 40 respondents. Validity and reliability tests ensured the accuracy and consistency of the research instrument, while multiple linear regression analysis revealed that price does not significantly affect customer loyalty. However, service quality and customer experience were found to have a significant positive impact. Simultaneously, the combination of price, service quality, and customer experience influences customer loyalty. The findings underscore the critical role of service quality and customer experience in fostering customer loyalty, particularly in the context of Panjol Workshop.